Computer Network Security - Sadiqui, Ali (Wiley-ISTE ; John Wiley & Sons, Inc., 2020)
Developed in collaboration with a training and certification team from Cisco, Computer Network Security is an exploration of the state-of-the-art and good practices in setting up a secure computer system. Concrete examples are offered in each chapter, to help the reader to master the concept and apply the security configuration. This book is intended for students preparing for the CCNA Security Exam (210-260 IINS) ' whether at professional training centers, technical faculties, or training centers associated with the 'Cisco Academy' program. It is also relevant to anyone interested in computer security, be they professionals in this field or users who want to identify the threats and vulnerabilities of a network to ensure better security.